2001
DOI: 10.1093/oxfordjournals.molbev.a003854
|View full text |Cite
|
Sign up to set email alerts
|

Complete Sequence of the Mitochondrial Genome of the Tapeworm Hymenolepis diminuta: Gene Arrangements Indicate that Platyhelminths Are Eutrochozoans

Abstract: Using "long-PCR," we amplified in overlapping fragments the complete mitochondrial genome of the tapeworm Hymenolepis diminuta (Platyhelminthes: Cestoda) and determined its 13,900-nt sequence. The gene content is the same as that typically found for animal mitochondrial DNA (mtDNA) except that atp8 appears to be lacking, a condition found previously for several other animals. Despite the small size of this mtDNA, there are two large noncoding regions, one of which contains 13 repeats of a 31-nt sequence and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 37 publications
7
78
0
1
Order By: Relevance
“…Using a similar approach, we have inferred that the initiation codon of cox1 in the cestode H. diminuta is GTT (Le et al, 2002b) (Table 1) thus agreeing with von Nickisch-Rosenegk et al (2001). In the latter paper, the initiation codon for nad4 is stated to be ATT.…”
Section: Discussionsupporting
confidence: 57%
“…Using a similar approach, we have inferred that the initiation codon of cox1 in the cestode H. diminuta is GTT (Le et al, 2002b) (Table 1) thus agreeing with von Nickisch-Rosenegk et al (2001). In the latter paper, the initiation codon for nad4 is stated to be ATT.…”
Section: Discussionsupporting
confidence: 57%
“…In the cases where it has been studied, all genes on each strand are transcribed together (Clayton 1992), so selection on gene arrangements is expected to be minimal. A summary of the evolutionary relationships convincingly demonstrated by this type of data (and in many cases left unresolved by all other studies) is found in Boore (2006), but here are a few of the more significant conclusions of deepbranch phylogenetic relationships: (i) the superphylum Eutrochozoa includes cestode platyhelminths (von von Nickisch-Rosenegk et al 2001) and the phylum Phoronida (Helfenbein & Boore 2004); (ii) Sipuncula is closely related to Annelida rather than to Mollusca (Boore & Staton 2002); (iii) Annelida is more closely related to Mollusca than to Arthropoda (Boore & Brown 2000); (iv) Arthropoda is monophyletic and, within this phylum, Crustacea is united with Hexapoda to the exclusion of Myriapoda and Onychophora (Boore et al 1995 and (v) Pentastomida is not a phylum, but rather a type of crustacean, and joins with Cephalocarida and Maxillopoda to the exclusion of other major crustacean groups (Lavrov et al 2004).…”
Section: Comparisons Of Mitochondrial Genomes Have Laid the Foundationmentioning
confidence: 58%
“…We amplified a portion of the mitochondrial (mtDNA) cytochrome oxidase I (COI; 369 bp) gene and ribosomal subunits (rRNA; approx. 810 bp) from the nematodes and cestodes, respectively, using primers COI-F/COI-R [23] and Hym16sF/Hym12sR [24]. Polymerase chain reaction (PCR) conditions were as in Galbreath et al [25], except for the annealing temperature (508C).…”
Section: (A) Data Collectionmentioning
confidence: 99%